2011
DOI: 10.1111/j.1468-0424.2011.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

The Early Quakers, the Peace Testimony and Masculinity in England, 1660-1720

Abstract: As Karen Harvey and Alexandra Shepard have asserted, most research into the history of masculinity has concentrated on dominant groups, while more work is needed on the range of codes of behaviour available to other men. Arguably, no aspect of seventeenth‐century Quaker behaviour ran more contrary to dominant norms than the insistence on pacifism and rejection of violence. This article considers Friends’ pacifism and its relation to masculinity, including its implications for local society, showing how it rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Here the legally required shift to monogamy necessitated new models of Mormon manhood marked by the dominant cultural virtues of business, patriotism and good citizenship rather than by polygamy. 38 Alex Shepard and Garthine Walker have observed that cultural historians' preference for synchronic readings of the multiple meanings of masculinity or femininity has tended to forestall diachronic analyses of gender's role as a catalyst for historical change. 39 Several articles in this special issue interrogate conventional readings of historical periods such as the Renaissance, or map longer-term shifts in legislative attitudes to, and textual representations of, specific religious traditions such as Hinduism, Buddhism and Confucianism.…”
Section: Past Perspectivesmentioning
confidence: 99%
“…Here the legally required shift to monogamy necessitated new models of Mormon manhood marked by the dominant cultural virtues of business, patriotism and good citizenship rather than by polygamy. 38 Alex Shepard and Garthine Walker have observed that cultural historians' preference for synchronic readings of the multiple meanings of masculinity or femininity has tended to forestall diachronic analyses of gender's role as a catalyst for historical change. 39 Several articles in this special issue interrogate conventional readings of historical periods such as the Renaissance, or map longer-term shifts in legislative attitudes to, and textual representations of, specific religious traditions such as Hinduism, Buddhism and Confucianism.…”
Section: Past Perspectivesmentioning
confidence: 99%